Graphene oxide as a radiation sensitive material for XPS dosimetry. (March 2020) - Torrisi, L.; Silipigni, L.; Cutroneo, M.; Torrisi, A.
Abstract: The suitability of graphene oxide (GO) foils as radiation sensitive materials for soft X-ray irradiation is investigated by means of X-ray photoelectron spectroscopy (XPS). In particular GO micrometric foils have been irradiated by soft X-rays at a 1486.6 eV energy at high flux (>10 12 photons/cm 2 s) in ultra-high vacuum. The XPS analysis of the carbon-carbon (CC) and the carbon-oxygen links (CO) characterizes the composition of the first layers of the GO foils. The CC/CO ratio of the high-resolution C1s XPS spectrum is used as dosimetric index. The incident X-ray photons, proportionally to their fluence, partially reduce GO foils decreasing the amount of oxygen groups chemically bonded to carbon network. This decrease causes an increase on the CC/CO ratio that is correlated to the irradiation time, i.e. to the dose absorbed by the GO foil, showing a linear increment with the dose. Our preliminary investigations indicate that GO can be employed to realize a thin foil dosimeter giving a linear response to the absorbed dose in the (275.76 kGy ÷ 8.02 MGy) range. The absorbed dose can be also evaluated by measuring the C/O ratio from the C1s and O1s XPS spectra analysis or with different techniques, as discussed in the paper. Highlights: Graphene oxide can be reduced by ionizing radiations. The reduction effect is proportional to the dose absorbed by the graphene oxide. XPS analysis permits to measure the graphene oxide reduction. A reduction increasing linearly with soft X-ray absorbed dose between 276 kGy and 8.0 MGy is measured.